2015
DOI: 10.1182/blood-2015-01-623645
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic marrow infiltration reveals a novel role for Egr3 as a potent inhibitor of normal hematopoietic stem cell proliferation

Abstract: Key Points Increased quiescence of HSCs and HPCs in leukemogenesis, and reversible suppression of HSCs was observed in leukemic bone marrow. A novel inhibitory role of Egr3 in HSC proliferation was revealed by leukemic infiltration in bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
124
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 39 publications
12
124
1
2
Order By: Relevance
“…Unlike the depletion of highly susceptible HSPC, HSC have proved to be more resilient during leukemic invasion, and multiple groups reported the relative accumulation of primitive hematopoietic cells in both murine models and xenograft studies [8,15,16,[21][22][23]. Unlike the depletion of highly susceptible HSPC, HSC have proved to be more resilient during leukemic invasion, and multiple groups reported the relative accumulation of primitive hematopoietic cells in both murine models and xenograft studies [8,15,16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the depletion of highly susceptible HSPC, HSC have proved to be more resilient during leukemic invasion, and multiple groups reported the relative accumulation of primitive hematopoietic cells in both murine models and xenograft studies [8,15,16,[21][22][23]. Unlike the depletion of highly susceptible HSPC, HSC have proved to be more resilient during leukemic invasion, and multiple groups reported the relative accumulation of primitive hematopoietic cells in both murine models and xenograft studies [8,15,16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…By simply removing the leukemic-effect terms from the model while keeping everything else unchanged, we could see that the normal kinetics, ie, hematopoietic cells as well as HSCs/HPCs were maintained at nearly steady levels [11], were reproduced (Additional file 2: Figure S2). Thus the model not only accurately represented the leukemia-conditioned hematopoietic dynamics; it could also faithfully reflect the situation under the normal condition.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an even more interesting observation indicated that except for pre-established leukemic disease, primary leukemia-initiating cells (L-ICs) were consistently outperformed by normal cord blood (CB) CD341 cells for BM niche occupancy in a cell dose dependent manner [32]. Notably, the results achieved by both of these studies might be explained by the recent observation that leukemic infiltration can induce progressive HSC quiescence by down-regulating cell-cycle genes and up-regulating several genes including Hes-1 and Egr3 [33]. However, in mice transplanted with AML, knock-down experiments have revealed that only Egr3 is responsible for HSC quiescence, an event that targets marrowresident but not spleen-resident HSCs.…”
mentioning
confidence: 77%